Ensino e aprendizagem de logaritmos através da resolução de problemas - Forest, Marciano (2014)
In order to improve the teaching and learning of mathematics at schools, we seek to investigate how to make it understandable and interesting study of logarithms in high school and what’s the possibility of using the Problem Solving Methodology for it. The methodological approach of the research comprised theoretical studies on the Troubleshooting and teaching methodology; detailed on the powers and properties studies as well as logarithms; development and implementation of a sequence of learning problems involving various types; analysis and discussion of the results listed. The problems have been arranged in a way that students might work with all concepts and properties of logarithms required for high school. The sequence was applied for 23 students from the first year of high school in a cooperative school called Intelectus in Xanxere SC. For this, it was used 15 lessons of 50 minutes each, 13 for applying the teaching sequence and two of them for the application of the evaluative tests. Most of the activities were conducted in groups of two or three students. The results were obtained through the qualitative analysis of daily notes, which were recorded by the teacher researcher after each meeting, qualitative analysis of a questionnaire answered by the students at the end of the work and quantitative analysis of the tests. The results showed that teaching logarithms by Troubles hooting sparked off interest in students and contributed to learning occurred according to the expected. Moreover, the work contributes to the continuing education of teachers, improving and complementing the teaching sequence for future new classes of applications.